2018
DOI: 10.1080/03057240.2018.1482531
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the divergences and convergences of trait empathy across two cultures

Abstract: Neuroscience at the University of Alabama. Her research interests include cultural differences in empathic behavior, personality and social development in adolescence, social neuroscience, and personality assessment. She is currently working on neural correlates of people's empathetic responses in social settings and evaluating the psychometric properties of psychological questionnaires. Behzad Mansouri is a doctoral student in Curriculum and Instruction at the University of Alabama. His research interests inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Both groups reported to have higher affective empathy than cognitive empathy. This result was in line with previous study in which American college students answered the IRI selfreported questionnaire and had a higher score on affective empathy (Yaghoubi Jami et al, 2019). On the other hand, having first-hand experience of psychological pain did affect situational cognitive empathy; those with an experience of psychological pain reported to have higher ability in understanding another individual in psychologically painful condition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both groups reported to have higher affective empathy than cognitive empathy. This result was in line with previous study in which American college students answered the IRI selfreported questionnaire and had a higher score on affective empathy (Yaghoubi Jami et al, 2019). On the other hand, having first-hand experience of psychological pain did affect situational cognitive empathy; those with an experience of psychological pain reported to have higher ability in understanding another individual in psychologically painful condition.…”
Section: Discussionsupporting
confidence: 91%
“…Although the present study applied Type III Sum Squares, the suggested analytical approach for unbalanced sample sizes (Pituch and Stevens, 2015), the present study failed to explore gender differences in participants' responses. There is numerous theoretical and empirical evidence showing gender effect on empathic responses (Yaghoubi Jami et al, 2019); thus, future studies may benefit from having balanced number of male and female participants in exploring the relationship between prior psychological pain and empathy.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…This is especially true concerning empathy, as in the present study females were found to report higher levels of empathy as compared to males. More recent studies show that emotional empathy continues to show a female bias (Jami, Mansouri, Thoma, & Han, 2018) and also increases in older people, whereas cognitive empathy has been found to decrease with age. Such developments may also influence levels of resilience and gratitude (Khanjani et al 2015).…”
Section: Summary Limitations and Future Directionsmentioning
confidence: 99%
“…The current study differs from previous studies in three ways. First, culture is a multidimensional construct (Jami et al, 2018); nevertheless, in previous Western–Asian cross-cultural studies of self-report empathy, the participant culture was identified only according to a single aspect, such as, nationality (e.g., Kaelber and Schwartz, 2014), ethnicity (e.g., Xu et al, 2009), or country of birth and growing up (e.g., Cassels et al, 2010). With reference to both the definition of culture and these previous studies, culture is defined as a string of simple proxies in the current study, including nationality (Australians or Mainland Chinese), ethnicity (Caucasians or Han Chinese), and country of birth and main place of growing up (Australian and Mainland China).…”
Section: Introductionmentioning
confidence: 99%